Effect of Epigallocatechin-3-Gallate (EGCG) on The Number of Lymphocyte Cells in Inflammation of Pulp with Mechanical Injury - Kun Ismiyatin; Latief Mooduto; Putri Dea Amani Faadhilah (Universitas Airlangga, 2020)
Background: Pulpitis is an inflammatory pulp that can caused by pulp perforation by mechanical injury. Emergency treatment of pulpitis is using Eugenol. High concentrations of Eugenol have a cytotoxic effect that causes local necrosis and inhibits the healing process. Because of negative effects from eugenol, then it’s necessary to consider a new ingredient with minimal side effects, and it’s epigallocatechin-3-gallate (EGCG) in green tea. As a polyphenol, it has good antioxidant effect and plays a role in shortening the duration of inflammation by radical scavenging against Nitric Oxide so that NO levels rapidly decrease which causes migration of neutrophil cells to the area of injury will decrease and the inflammatory process faster so that the healing process become faster. Lymphocyte is plays a role in tissue repair. Purpose: to explain the effect of EGCG hydrogel on the number of lymphocyte cells in pulp inflammation with mechanical injury. Methods: The study used 24 Wistar rats divided into four groups, namely control (C), and 3 groups of treatment (T1, T2, T3). Each group consisted of 6 rats prepared, then EGCG hydrogel 60 ppm was named T1, EGCG hydrogel 90 ppm was named T2, EGCG hydrogel 120 ppm was named P3. On the 3rd day, Wistar rats were decapitated for HPA preparations. Results: This study showed a significant difference in each group (p < 0.05) using One-Way Anova analysis. Conclusion: EGCG hydrogel 90 ppm is effective in increasing the number of lymphocyte cells in inflammation of the pulp with mechanical injury.